Criminalization and violence against the South American transvestite / trans migrant population residing in the Metropolitan Area of ​​Buenos Aires (Delito y Sociedad, 2021)
The article describes the processes of violence and criminalization experienced by the South American transvestite / trans migrant population in the AMBA (Metropolitan Area of  Buenos Aires), during the period 2017-2019. The migratory projects of South American transvestites / trans have a set of dimensions and imply going through a series of moments for their realization. When these people are inserted into the host society, they go through a set of experiences, among them, they experience different violence from the security forces and criminalization processes of the Judicial Power. The methods used were grounded theory, ethnography, and the life story. The research techniques were mainly the in-depth interview and participant observation. A theoretical sample was constructed that included 44 cases, allowing to discover a multiplicity of analysis categories as well as properties and dimensions that concluded in the theoretical saturation. The research found that in the processes of violence and criminalization, the migratory condition and gender identity of the interviewees interact in a matrix of domination that accentuates the vulnerabilities they experience.
Keywords: criminalization; violence; transvestites; trans; migrations